2015
DOI: 10.1016/j.elecom.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Improved Pt-utilization efficiency of low Pt-loading PEM fuel cell electrodes using direct membrane deposition

Abstract: Direct membrane deposition was used to produce record platinum catalyst utilization efficiency polymer electrolyte membrane fuel cells. The novel membrane fabrication technique was applied to gas diffusion electrodes with low Pt-loadings of 0.102 and 0.029 mg/cm 2 . Under oxygen atmosphere and 300 kPa abs total pressure, 88 kW/g Pt cathodic catalyst utilization efficiency with a symmetrical Pt-loading of 0.029 mg/cm 2 on the anode and cathode side was achieved. This is 2.3 times higher than the Pt-utilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 16 publications
4
41
0
Order By: Relevance
“…In general, the ACLJS method offers excellent performance in terms of both current density at 0.7 V and peak power density, with 1.9 A/cm 2 [38][39][40] However, it should be noted that RSDT is very expensive to implement on the laboratory scale (∼$150,000 USD) and has a significant number of adjustable parameters, which may limit its widespread application in a university or R&D setting, though it remains promising at larger scales. By comparison, the ACLJS is a fairly economic process, where only a small amount of electricity and nitrogen gas are consumed.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the ACLJS method offers excellent performance in terms of both current density at 0.7 V and peak power density, with 1.9 A/cm 2 [38][39][40] However, it should be noted that RSDT is very expensive to implement on the laboratory scale (∼$150,000 USD) and has a significant number of adjustable parameters, which may limit its widespread application in a university or R&D setting, though it remains promising at larger scales. By comparison, the ACLJS is a fairly economic process, where only a small amount of electricity and nitrogen gas are consumed.…”
Section: Resultsmentioning
confidence: 99%
“…This MEA fabrication method enables very low membrane resistances below 13 mU cm 2 and therefore high fuel cell power densities beyond 4.0 W/cm 2 with H 2 /O 2 as feed gases at 300 kPa abs and beyond 1.3 W/cm 2 under stoichiometric 1.2/2.0 H 2 /air operation at 300 kPa abs . The high performance was linked to a very low membrane thickness of about 12 mm and an improved interface between catalyst layer and the membrane itself [1,2]. Despite the high power densities another significant difference was identified compared to conventionally cast membranes: The cell polarization measurements in the work of Klingele et al [1] reveal that the ionic resistance increased only slightly at low humidification.…”
Section: Introductionmentioning
confidence: 94%
“…1b) was tightened with a torque of 1 Nm. A detailed description of the sample preparation including the printing process was published previously [1,2]. As reference, we used an N-112 Nafion ® membrane, coated with catalyst layers of identical Pt loading i n t e r n a t i o n a l j o u r n a l o f h y d r o g e n e n e r g y 4 1 ( 2 0 1 6 ) 1 1 4 1 2 e1 1 4 1 7 and stacked between the same gas diffusion media (Paxitech SAS).…”
Section: Sample Preparation and Fuel Cell Operationmentioning
confidence: 99%
“…In this article, we have demonstrated that this resistance is a mass-transport resistance (MTR), which follows a diffusion-type mass 9 dependence. Furthermore, it is shown how a facile hydrogen-pump experiment can be easily employed to quantify this effect, thereby ruling out activation processes, water production, oxide effects, possible peroxide formation, and enhanced heat generation during oxygen limiting-current experiments at low potentials.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Regrettably already for loadings below 0.10 mg Pt /cm² at the cathode side, the performance suffers quite drastically due to a poorly understood local resistance, which is thought to be related to an increased local mass-transport resistance (MTR), although other causes have been proposed as well. [2][3][4][5][6][7][8][9][10][11][12][13] In terms of physical interpretation, the MTR represents the local resistance of a reactant molecule towards reaching an active reaction site, which becomes more significant as the number of reaction sites decrease but the desired overall reaction rate remains the same.…”
Section: Introductionmentioning
confidence: 99%